Time Series Water Body Analysis Through Planet Satellite Imagery: A Coastal Urban Case Study (2024)
Many water bodies play a crucial role as receiver of several urban basins within the water system of a city, these urban basins often face challenges of pollution and reduction in water flow, such as, the case of the Juan Angola channel in the city of Cartagena, Colombia. Current remote sensing strategies using Landsat and Sentinel-2 satellite imagery, lack the necessary spatial resolution to adequately study such as water bodies. In contrast, higher spatial resolution data, such as the PlanetScope one, allows for better spatial and temporal details. Nevertheless, PlanetScope does not count with the same spectral resolution as Landsat and Sentinel-2, requiring of further processings to extract relevant information. In this paper, we used PlanetScope satellite images, processed through computer vision techniques, to analyze the evolution of the Juan Angola channel, Laguna del Cabrero and Chambac´u over time. Our approach involved extracting water areas from PlanetScope images and comparing these over different periods. Preliminary findings revealed noticeable variations in the area of the channel due to factors such as rainfall and possible illegal human invasion, as well as, the increment in level of contamination observed by means of the Normalized Difference Turbidity Index (NDTI). The images used from PlanetScope offered a more detailed time-series analysis of different hydrographic areas, which is particularly pertinent in the Juan Angola channel.